Differences in the use of vision and proprioception for postural control in autism spectrum disorder. (29th October 2015) - Morris, S.L.; Foster, C.J.; Parsons, R.; Falkmer, M.; Falkmer, T.; Rosalie, S.M.
Highlights: Vibration was used to induce a postural illusion in typical adults and adults with ASD. With vision removed, both groups responded to the postural illusion by leaning forward. Typical adults corrected the lean using vision while adults with ASD did not. In ASD somatosensory information dominates over optic flow regarding the position of the head. Abstract: Background : People with autism spectrum disorders (ASDs) also have poorer fundamental motor skills. The development of postural control underlies both social and motor skills. All three elements are facilitated by the active use of visual information. This study compares how adults with ASD and typically developed adults (TDAs) respond to a postural illusion induced using neck vibration. Adults with ASD unlike the TDA, were not expected to correct the illusion using vision. Methods : The study used intermittent (15off, 5on) posterior neck vibration during 200 s of quiet stance to induce a postural illusion. In TDAs and only in the absence of vision this protocol induces a forward body lean. Participants (12 ASD, 20 TDA) undertook four conditions combining vibration and visual occlusion. Results : As predicted, TDA were only affected by the postural illusion when vision was occluded (vibration condition: vision occluded ( n = 1) p = 0.0001; vision available ( n = 3) p > 0.2466). Adults with ASD were affected by the postural illusion regardless of the availability of vision (all conditions p < 0.0007). Conclusions : Our findings indicated the adults with ASD did not use visual information to control standing posture. In light of existing evidence that vision-for-perception is processed typically in ASD, our findings support a specific deficit in vision-for-action. These findings may explain why individuals with ASD experience difficulties with both social and motor skills since both require vision-for-action. Further research needs to investigate the division of these visual learning pathways in order to provide more specific intervention opportunities in ASD.